1st Annual report and accounts 1969 - 70 - South-Eastern State Agricultural Development Corporation. - South-Eastern State Agricultural Development Corporation (Calabar: South-Eastern State Agricultural Development Corp, 1971)
The first Annual Report of the South-Eastern State Agricultural Development Corporation should more accurately cover the period August 1969 to March 31, 1970. This report, will as far as it relates to this period provide only such information as can be found in records available to the corporation
osc 21/05/2019
Arch
Keywords: Agricultural Economics; Economic conditions; Nigeria